Calorie restriction reverses age‐related alteration of cavernous neurovascular structure in the rat. (25th July 2017) - Limanjaya, A.; Song, K.‐M.; Choi, M.‐J.; Ghatak, K.; Minh, N. N.; Kang, D. H.; Ock, J.; Yin, G. N.; Chung, H. Y.; Ryu, J.‐K.; Suh, J.‐K.
Summary: Calorie restriction (CR) refers to a reduction of calorie intake without compromising essential nutrients to avoid malnutrition. CR has been established as a non‐genetic method of altering longevity and attenuating biological changes associated with aging. Aging is also an important risk factor for erectile dysfunction. The aim of this study was to examine whether CR diet can reverse the age‐related alterations of erectile tissue in the aged rat. Four groups of rats were used: young rats (7 months) + ad libitum, aged rats (22 months) + ad libitum, young rats + CR diet, and aged rats + CR diet. The ad libitum group had free access to both food and water, and CR groups were fed 60% of the food intake of their ad libitum littermates, starting from 6 weeks before sacrifice. The penis was harvested and stained with antibodies to von Willebrand factor, smooth muscle α‐actin, platelet‐derived growth factor receptor‐β, phospho‐eNOS, nNOS, and neurofilament. We also performed Masson trichrome staining and TUNEL assay. The blood samples were collected for the measurement of serum total testosterone level. The contents of endothelial cells, smooth muscle cells, pericytes, and neuronal cells as well as serum testosterone levels were significantly lower in the penis of aged rats than in their young littermates. CR significantly restored cavernous endothelial cells, smooth muscle cells, pericytes, and neuronal cell contents and decreased cavernous endothelial cell apoptosis and fibrosis in both young and aged rats. CR also increased serum testosterone level in aged rats, but not in young rats. CR successfully improved age‐related derangements in penile neurovascular structures and hormonal disturbance. Along with a variety of lifestyle modifications, our study gave us a scientific rationale for CR as a non‐pharmaceutical strategy to reprogram damaged erectile tissue toward neurovascular repair in aged men.